PH responsiveness of multilayered films and membranes made of polysaccharides - Silva, J. M. (2015)
We investigated the pH-dependent properties of multilayered films made of chitosan (CHI) and alginate (ALG) and focused on their postassembly response to different pH environments using a quartz crystal microbalance with dissipation monitoring (QCM-D), swelling studies, Î¶ potential measurements, and dynamic mechanical analysis (DMA). In an acidic environment, the multilayers presented lower dissipation values and, consequently, higher moduli when compared with the values obtained for the pH used during the assembly (5.5). When the multilayers were exposed to alkaline environments, the opposite behavior occurred. These results were further corroborated by the ability of this multilayered system to exhibit a reversible swellingâ deswelling behavior within the pH range from 3 to 9. The changes in the physicochemical properties of the multilayer system were gradual and different from those of individual solubilized polyelectrolytes. This behavior is related to electrostatic interactions between the ionizable groups combined with hydrogen bonding and hydrophobic interactions. Beyond the pH range of 3â 9, the multilayers were stabilized by genipin cross-linking. The multilayered films also became more rigid while the pH responsiveness conferred by the ionizable moieties of the polyelectrolytes was preserved. This work demonstrates the versatility and feasibility of LbL methodology to generate inherently pH stimulus-responsive nanostructured films. Surface functionalization using pH responsiveness endows several biomedical applications with abilities such as drug delivery, diagnostics, microfluidics, biosensing, and biomimetic implantable membranes.